Nonlinear System Identification : NARMAX Methods in the Time, Frequency, and Spatio-Temporal Domains. - Billings, Stephen (Wiley, 2013)
This book helps practitioners and researchers find ways to solve difficult nonlinear system identification problems using the well-established NARMAX method. It is a description of a class of system identification algorithms that can be used to identify nonlinear dynamic models from recorded data. Written with an emphasis on making algorithms and methods accessible so that they can be applied and used in practice, this book also addresses frequency and spatio-temporal methods rarely covered elsewhere, and which can provide significant insights into complex system behaviours.